Change of mineral and organic nitrogen forms in a long term fertilization experiment (literature) - Horváth, Judit; Kátai, János (Acta Agraria Debreceniensis, 2014)
The research topic has timeliness, since the rational utilization and protection of the soil, besides the conservation of its diverse functions is part of the sustainable development. Research of the long-term experiments is esentially important, because it can model the term effects in the same place, under the same conditions. If we want to get accurate informations about the occured changes, way and danger of changes, we should track the resupply and effect of the mineral nutrients and the removed quantity of nutrients with the harvest. Nitrogen is an essential element for living organisms, it is present in the soil mainly in organic form. In general only only a low percentage of the total nitrogent content can be used directly by plants in the soil. This inorganic nitrogen is produced by the transformation of organic contents through mineralization processes and it get into the soil by the fertilization. The plants incorporote the mineral nitrogen into our bodies. This is how nitrogen turnover is realized when mineral forms become organic and organic forms become mineral.The purpose of our paper is to make a literature before our research.